Design and Development of a Free-Fall Experiment Apparatus Based on a Photodiode Sensor - Bayu Septiawan; Naufal Rizky Akbar; Fauzan Najib Habibi (Indonesian Journal of Educational Innovation, 2025)
The integration of technology in education, particularly through sensor- and microcontroller-based experimental tools, has proven effective in enhancing the accuracy and efficiency of science learning. This study aims to design a free-fall motion experiment apparatus utilizing a photodiode sensor and Arduino Nano to improve time and gravitational acceleration measurements. The design includes hardware components (electromagnetic ball release, laser, photodiode sensor, and LCD) and software using the Arduino IDE. Experiments at heights of 0.2 m, 0.4 m, and 0.6 m yielded average gravitational acceleration values of 9.715 m/s², 9.787 m/s², and 9.819 m/s², respectively, close to the theoretical value of 9.8 m/s² with low standard deviations (0.351, 0.323, 0.311) m/s². The sensor’s fast response (0.001 milliseconds) demonstrates the tool’s effectiveness in minimizing manual error. These findings suggest that integrating a photodiode sensor with an Arduino Nano can produce an accurate and efficient tool for physics experiments. Further development, such as automated height adjustment, is recommended to enhance measurement precision.